2020
DOI: 10.1136/openhrt-2020-001428
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in patients hospitalised with Coronavirus disease 2019 (COVID-19) infection

Abstract: ObjectiveAmong patients with Coronavirus disease 2019 (COVID-19), coronary artery disease (CAD) has been identified as a high-risk condition. We aimed to assess the clinical outcomes and mortality among patients with COVID-19 according to CAD status.MethodsWe retrospectively analysed data from patients with COVID-19 admitted to the Cremona Hospital (Lombardy region, Italy) between February and March 2020. The primary outcome was all-cause mortality. CAD was defined as a history of prior myocardial infarction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…In our study, it was 11/93 (11.8%). The average age of patients with CAD is known to be older with a male predominance [ 21 ]. Ninety percent of the patients with CAD in our study were males and their mean age was 14.4±7.3 years older than that of patients without CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, it was 11/93 (11.8%). The average age of patients with CAD is known to be older with a male predominance [ 21 ]. Ninety percent of the patients with CAD in our study were males and their mean age was 14.4±7.3 years older than that of patients without CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety percent of the patients with CAD in our study were males and their mean age was 14.4±7.3 years older than that of patients without CAD. Several studies have reported an increased risk of ARDS, CCU admission, need for ventilation, and death in patients with CAD with COVID-19 infection, however it is not very clear to what extent the increased risk is attributable to CAD as an independent risk factor [ 20 , 21 ]. The patients with CAD in our study had significantly higher risk of adverse outcome with respect to prolonged hospital admission, oxygen therapy, CCU admission, and death; multivariable regression analysis calculated an OR of 12.22 (95%CI 2.4-61.5, p<0.002) for failure to wean and delayed recovery in patients with CAD aged >50 years having multiple co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine hundred and sixteen potentially relevant studies were screened according to the inclusion and exclusion criteria. Finally, 23 studies with 108,745 COVID-19 patients 1 , 2 , 3 , 4 , 5 , 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were eligibly included in the present quantitative meta-analysis. The study characteristics are summarized in Table 1 .…”
mentioning
confidence: 99%
“…Consequently, as long as invasive assessment can be safely and timely performed, 4 we should go back to the “normal” guidelines supporting primary PCI and early invasive strategy for the majority of patients with ST‐elevation and non‐ST‐elevation ACS, respectively. Data suggest that patients with concomitant coronary artery disease and COVID‐19 have a threefold higher risk of mortality, 5 which is mainly explained by the burden of comorbidities. Hence, invasive angiography with the possibility of revascularization not only should not be withheld in COVID‐19 patients with ACS, but rather supported as the authors brilliantly did.…”
mentioning
confidence: 99%